The candidate - Redford, Robert 1936-; Boyle, Peter; Douglas, Melvyn 1901-1981; Coblenz, Werner 1917-1995; Ritchie, Michael 1938-2001 (Warner Entertainment, 1997)
Bill McKay is enlisted by campaign maestro Marvin Lucas to run for U.S. Senator. McKay agrees, but only if he can say exactly what he thinks. That approach is all well and good when McKay does not seem to have a chance, but things change when his honesty unexpectedly captivates the electorate. As McKay inches up in the polls, Lucas and company start to do what it takes to win, leaving McKay to ponder the consequences of his political seduction
Original: USA 1972
Keywords: Geschichte 1972; Feature films / United States; Political campaigns / Drama; Political campaigns -- United States -- Drama.; Presidents -- United States -- Election -- 1972 -- Drama.; Feature films.; Feature films -- United States; Political campaigns -- Drama; Wahlkampf; Präsidentenwahl; USA; Film; DVD-Video